TA'WIL AND NUSAIRISM IN EXTERNAL THOUGHT - Arpa, Abdulmuttalip; Ertaş, Kasım (GAZI UNIV, 2012)
NThere is no doubt that Batiniyya (external thought) is one of the issues under discussion for a long time in Islamic world. Batiniyya (external thought) is used for the expression of those who know the inner face of hidden things. They argue that each verse in the Qur'an has the outer, exoteric level of meaning (batin) as well as an esoteric (batini) level of meaning. This madhap believes that nobody knows the interpretation of the Qur'an except for innocent (masum) imams who have a secret and special bond and contact between God and themselves. Batiniyya, therefore, has been used to express this group of people. While claiming each verse in the Qur'an has a special interpretation, Batini mentality does not accept any border and limit for interpretation. It seems that a kind of ta'wil (interpretation) concept does not obey any rules dominant in the madhap. According to Batiniyyas, the Prophet stated only the external meanings of the verses, but the Imams know the true meaning of the verses. In this respect, those who know the true meaning of the Qur'an and are immensely familiar with esoteric meanings are just Imams. In the beginning, Batiniyya emerged as Ismaelite and Jafariyya and then was manifested under various disguises in Muslim world. Another mystic movement and philosophy which emerged in this context and survived until today, is Nusayriyya. This study, therefore, first deals with how the idea of ta'wil emerged in Islamic thought, and secondly how it was perceived and used in Sunni and Mini philosophy. At first, short information about Nusayriyya will be given and then the study will focus on its ideas of faith, the structure and dimensions of methods of ta'wil which is used in the formation of this madhab.
Keywords: Islam; Batiniyya; Nusayriyya; Tawil